2021
DOI: 10.1186/s12864-021-07369-9
|View full text |Cite
|
Sign up to set email alerts
|

BSR-Seq analysis provides insights into the cold stress response of Actinidia arguta F1 populations

Abstract: Background Freezing injury, which is an important abiotic stress in horticultural crops, influences the growth and development and the production area of kiwifruit (Actinidia Lind1). Among Actinidia species, Actinidia arguta has excellent cold resistance, but knowledge relevant to molecular mechanisms is still limited. Understanding the mechanism underlying cold resistance in kiwifruit is important for breeding cold resistance. Results In our study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The enzyme BAM accumulates SS under stress conditions 41 . Cold stress increased the content of soluble sugar and the activity of β-amylase 42 . Our study showed that the content of soluble sugar increased during cold stress, and BAM5(Bra038088) was down-regulated in L7 d/Le d and L7 CK/Le CK.…”
Section: Discussionmentioning
confidence: 97%
“…The enzyme BAM accumulates SS under stress conditions 41 . Cold stress increased the content of soluble sugar and the activity of β-amylase 42 . Our study showed that the content of soluble sugar increased during cold stress, and BAM5(Bra038088) was down-regulated in L7 d/Le d and L7 CK/Le CK.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Maschietto et al (2015) demonstrated that plant resistance responses were mounted between 7 and 14-days post-inoculation (dpi). In this study, we used a bulk-segregant RNA-seq (BSR) approach to compare different inbred pools 10 dpi, since it would allow us to simultaneously identify differentially expressed genes (DEGs) and polymorphic DNA markers related to fumonisin accumulation ( Du et al, 2017 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity is an important indicator of cell membrane stability and fluidity and identifies the cold resistance of seedlings. The results showed that under low temperature stress, young cotton seedling electrical conductivity enzyme activity of peroxidants and soluble sugars increased, and root activity decreased, while young cotton seedling electrical conductivity and root activity decreased less in low temperature resistant varieties ( Anastasia et al, 2010 ; Lin et al, 2021 ). The content of active and soluble sugars increased significantly.…”
Section: Research Progress On Cotton Stress Resistance Breedingmentioning
confidence: 99%